Transforming Taxation: Unlocking Efficiency and Resilience Through Digitalization - Ratih Damayanti; Muhammad Azil Masykur; Feiruz Rachmita Alamsyah; Ali Masyhar Mursyid; Dani Muhtada (The Indonesian Journal of International Clinical Legal Education, 2024)
The digitalization of tax administration aims to improve service efficiency and institutional resilience by leveraging advanced technologies. By integrating digital tools, tax administration processes can be streamlined, reducing errors and enhancing taxpayer compliance. This research is a qualitative descriptive study that relies on secondary data collection. However, the digitalization of tax administration faces several challenges, such as uneven technological infrastructure, internal resistance to change, and cybersecurity threats. This study explores various digitalization initiatives, the challenges encountered during implementation, and the resulting benefits in terms of service optimization and institutional resilience. The findings indicate that digital transformation is a critical step towards achieving a more effective and resilient tax administration system. Therefore, the strategy of implementing tax reform for the digital era is appropriate. This involves increasing taxpayer trust and compliance by enhancing the capacity and integrity of the Directorate General of Taxes. The research also reveals that tax reform faces growing challenges in the digital age. Digitalization is not only a challenge for improving the capabilities and integrity of tax authorities but also for modernizing tax human resource systems and controls. These reforms are essential to building strong institutions capable of navigating the complexities of the digital era.